Triazole-based novel bis Schiff base colorimetric and fluorescent turn-on dual chemosensor for Cu2+ and Pb2+: application to living cell imaging and molecular logic gates. Issue 44 (19th August 2019) - Rout, Kalyani; Manna, Amit Kumar; Sahu, Meman; Mondal, Jahangir; Singh, Sunil K.; Patra, Goutam K.
Abstract : A novel triazole-based bis Schiff base colorimetric and fluorescent chemosensor (L ) has been designed, synthesized and characterized. The chemo-sensorL shows its application potential in the detection of Cu 2+ and Pb 2+ in living cells and building molecular logic gate. Abstract : A triazole-based novel bis Schiff base colorimetric and fluorescent chemosensor (L ) has been designed, synthesized and characterized by elemental analysis, 1 H-NMR, ESI-MS, FTIR spectra and DFT studies. The receptorL showed selective and sensitive colorimetric sensing ability for Cu 2+ and Pb 2+ ions by changing color from colorless to yellow and light yellow respectively in CH3 OH–tris-buffer (1 : 1, v/v). However, it displayed strong fluorescence enhancement upon the addition of both Cu 2+ and Pb 2+ ions, attributed to the blocking of PET. The fluorometric detection limits for Cu 2+ and Pb 2+ were found to be 12 × 10 −7 M and 9 × 10 −7 M and the colorimetric detection limits were 3.7 × 10 −6 M and 1.2 × 10 −6 M respectively; which are far below the permissible concentration in drinking water determined by WHO. Moreover, it was found that chemosensorL worked as a reversible fluorescence probe towards Cu 2+ and Pb 2+ ions by the accumulation of S 2− and EDTA respectively. Based on the physicochemical and analytical methods like ESI-mass spectrometry, Job plot, FT-IR, 1 H-NMR spectra and DFT studies the detection mechanism may be explained as metal coordination, photoinduced electron transfer (PET) as well as an internal charge transfer (ICT) process. The sensor could work in a pH span of 4.0–12.0. The chemosensorL shows its application potential in the detection of Cu 2+ and Pb 2+ in real samples, living cells and building of molecular logic gate.